THE MEDIATING EFFECT OF WORKPLACE ENVIRONMENT ON EXECUTIVES’ PERFORMANCE IN MANUFACTURING INDUSTRIES AT KULIM HI-TECH PARK KULIM KEDAH, MALAYSIA - Bokhori Md Amin (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Workplace environment plays the important role in addressing issues related to job performance. Therefore, the purpose of this study is to assess the extent of the mediating effect of workplace environment and its contribution to the performance of executive in manufacturing industries. A questionnaire was designed for data collection to measure workplace environment related psychology mental and physical workplace on executives’ performance. Data were collected among executives in manufacturing industries at Kulim Hi-tech Park, Kulim, Kedah, Malaysia. Stratified sampling method was used to collect data and the data obtained were analyzed using SmartPls 3.7.8. The results of the study found that there is a significant relationship between psychology mental and physical workplace on executives’ performance in manufacturing industries. It is proved from SmartPls analysis shown that all independent variables have a significant impact on executives’ performance in manufacturing industries. The limitation of the research only covers the manufacturing industries. Another limitation is the respondents only included executives. Apart from these limitations, this research can give the strong impact to the top management of manufacturing industries to design the strategy of workplace environment in order to be more effective in improving the work performance of executives.